Implementasi pendidikan karakter berbasis Pesantren pada siswa-siswi program keagamaan di Madrasah Aliyah Sunan Pandanaran Sleman - Rohili, Ili; Najib, Khotim Hanifudin; Fitriyah, Eka Laila; Alfina, Alisa (Bulletin of Educational Management and Innovation, 2024)
Purpose: This study discusses the planning, implementation, and evaluation of the implementation of boarding-based education on Sunan Pandanaran Aliyah Madrasah religious program students and how the results helped by considering the implementation of this pesantren-based character education. Method: This research is a field research, the data collection tools used are observation, interviews, and documentation. The research subjects were students of Sunan Pandanaran Aliyah Madrasah. This study discusses qualitative descriptive, namely research that discusses what phenomena are discussed by research in this case the students of Sunan Pandanaran Aliyah Madrasah in the implementation of boarding-based character education. Findings: The results of this study indicate that (a) pesantren-based character education planning is well integrated with the madrasah vision and mission announced on all subjects and the purpose of developing affective / physical aspects both spiritual and social. (b) Implementation of pesantren-based character education integrates character education in all subjects, according to the RPP made by each subject teacher, then the character education requested through explanations, providers of examples and challenges to facing challenges, habituation to noble behavior is done every day, and teachers and boarders provide good role models.